2005
DOI: 10.1590/s0102-69092005000300007
|View full text |Cite
|
Sign up to set email alerts
|

A política da avaliação de políticas públicas

Abstract: Em um plano normativo, a década de 1990 testemunhou, nas democracias ocidentais de uma maneira geral, e na América Latina particularmente, a busca de fortalecimento da "função avaliação" na gestão governamental. Com efeito, foram implementados, em diversos países da América Latina, sistemas de avaliação das políticas públi-cas de escopo variável. Tal processo tem sido justificado pela necessidade de "modernização" da gestão pública, em um contexto de busca de dinamização e legitimação da reforma do Estado.Os a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
133

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(170 citation statements)
references
References 23 publications
0
15
0
133
Order By: Relevance
“…Disagreeing with this assessment, Frey (2000) argues that Brazilian policy studies began only recently and have not, as yet, found an institutionalized academic or professional home. In their assessments of the public policy field, Melo (1999) and Faria (2005) have argued that knowledge about evaluation of public policies in Brazil is very limited. According to Bechelaine and Ckagnazaroff (2014), despite the growing interest in evaluating government programs in Brazil, there is a national shortage of theoretical studies to verify the use of such assessments as correction tools for improvement of public services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Disagreeing with this assessment, Frey (2000) argues that Brazilian policy studies began only recently and have not, as yet, found an institutionalized academic or professional home. In their assessments of the public policy field, Melo (1999) and Faria (2005) have argued that knowledge about evaluation of public policies in Brazil is very limited. According to Bechelaine and Ckagnazaroff (2014), despite the growing interest in evaluating government programs in Brazil, there is a national shortage of theoretical studies to verify the use of such assessments as correction tools for improvement of public services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The emergence of the systematic analysis of policies and programs was stimulated by multilateral organizations, which required evaluations as a condition for financing projects in the region (Faria, 2005). According to Ramos and Schabbach (2012) in the last decade major international institutions including the United Nations, World Bank, Organization for Economic Co-Operation and Development (OECD), and Inter-American Development Bank (IDB) have developed methodologies for evaluation of public policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Uma das maneiras de se pensar acerca da avaliação de políticas públicas, proposta por Derlien e citado por Faria (2005), é que entre os anos 1960 e 1990, os objetivos buscados com a avaliação teriam passado da função de informação para a realocação. ou seja, a função predominante nos anos de 1980 era a de alocar racionalmente os recursos.…”
Section: Propósitos E Importância Das Políticas Públicas Para O Setorunclassified
“…Ainda segundo Faria (2005), os avaliadores precisam se atentar na avaliação e cumprir seu papel sendo fieis aos reais objetivos e não se atentarem a usar a avaliação como uma oportunidade para resistir à reforma. Daí a importância dos avaliadores serem externos ao programa (auditores).…”
Section: Propósitos E Importância Das Políticas Públicas Para O Setorunclassified
“…Uma delas é considerá-la como um procedimento destinado a apontar resultados para possíveis intervenções, maximizando o gasto público nas suas diversas atividades. Ou como objeto da intervenção, fornecendo informações para aprimorar políticas ou a elaboração de novos projetos ou ainda como prestação de contas partindo do conceito de accountability (COSTA; CASTANHAR, 2003, THOEING, 2000, NEPP, 1999, FARIA, 2005.…”
Section: Avaliação De Políticas Públicas: Conceitos E Implicaçõesunclassified